Hassan Hanafi's Reformation in The Islamic World - Rufaiqoh, Elok; Sumbulah, Umi; Nuruddin, Ahmad; Hanisyi, Asmad; Arifin, Zainal (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2023)
This research analyzes Hassan Hanafi's liberation thoughts: Al-Turats wa Al Tajdid, hermeneutics of liberation, and the Islamic left. The method used in this research is library research with a descriptive-analytic method, namely using interpretive analysis of books by Hassan Hanafi as primary data and articles, research journals, and other scientific works related to the research object as secondary data. The research results show that Al Turats Wa Tajdid is a significant project in the revival of Islam. This Hanafi idea changed the concept of Islamic theology from theocentric to anthropocentric. The second is Hassan Hanafi's hermeneutics of liberation using three methods: 1) Historical-Criticism, 2) Eidetic-Conciusness, and 3) Practical-Conciusness. The third is the movement for the liberation of Islamic thought called the